R&D internationalization and innovation performance: the moderating role of financial slack - Dong, Xinyang (Transactions on Social Science, Education and Humanities Research, 2024)
Among enterprises in emerging economies represented by China, R&D internationalization is an important strategic choice, aiming to obtain advanced technological resources and achieve competitive advantages. Taking listed companies in the information transmission, software and information technology services, and scientific research and technology services industries in China from 2018 to 2022 as research objects, this paper explores the impact of R&D internationalization on innovation performance, and examines the moderating role of financial slack in this relationship from the perspective of slack resources in organizational theory. The results show that there is a positive relationship between R&D internationalization and innovation performance. Further research shows that from the perspective of organizational theory, financial slack will positively strengthen the role of R&D internationalization in promoting corporate innovation performance. This paper discusses the moderating role of financial slack in this relationship for the first time. The research results have important practical implications for enterprises in emerging economies to formulate R&D internationalization strategy and improve innovation performance.